Model - spatial approach to prediction of minimum wage - Monika Hadas-Dyduch (Institute of Economic Research (IER), 2016)
The aim of the article is to present the author's model for prediction of the minimum wage. The model is based on wavelet analysis and methods of adaptation. Use of multiresolution analysis for prediction of the minimum wage in combination with the method to compensate the exponential gave good results in terms of minimizing the error. Research the minimum wage is very important. It should be noted that, in 2014, the level of gross minimum wages across the EU Member States varied from 33 % to just over 50 % of average gross monthly earnings for those persons working in industry, construction or services.
Keywords: C5; F3; 330; wavelets; prediction; salary; minimum wage